Perception of animal welfare and its certification system by Brazilian consumers and dairy farmers - Comin, Vinicius Cardoso; Karsburg, Helena Fagundes; Souza, Bruna Maria Salotti De; Almeida, Henrique Meiroz De Souza [UNESP]; Neira, Ligia Maria; Rossi, Gabriel Augusto Marques (Cambridge University Press (CUP), 2022)
The practices adopted in dairy farms can positively or negatively affect the perception of consumers. To meet consumer expectations and improve the productivity of dairy farms, a welfare certification system has recently been initiated in Brazil. In this research communication we describe the perceptions of Brazilian consumers and farmers regarding the implementation of welfare certification systems and the most common practices that affect animal welfare on dairy farms. For this purpose, two semi-structured questionnaires were used: one applied to 409 consumers and the other to 158 dairy farmers. The results demonstrate that consumers are concerned with the adoption of welfare practices in animal husbandry at dairy farms, mainly on topics related to movement restriction and cow-calf separation. Thus, the majority of consumers state that they are willing to pay more for welfare-certified dairy products. In addition, most dairy farmers are interested in adopting a welfare certification system, especially if it could add value to the raw milk sold to industries. Veterinarians and animal scientists are important for disseminating animal welfare recommendations, and the consequences of its improper adoption need to be emphasized. Finally, dairy farms need improvements regarding environmental hygiene, thermal conditions, animal husbandry, health, and milking processes. In conclusion, consumers and farmers are interested in welfare systems and their certification, and there is a need for stakeholders to make welfare certification a reality in the Brazilian dairy supply chain.
Keywords: Bovine; dairy; milk; perception; welfare